Conflict between heterozygote advantage and hybrid incompatibility in haplodiploids (and sex chromosomes). Issue 19 (10th February 2018) - Ghenu, Ana‐Hermina; Blanckaert, Alexandre; Butlin, Roger K.; Kulmuni, Jonna; Bank, Claudia
Abstract: In many diploid species, the sex chromosomes play a special role in mediating reproductive isolation. In haplodiploids, where females are diploid and males haploid, the whole genome behaves similarly to the X/Z chromosomes of diploids. Therefore, haplodiploid systems can serve as a model for the role of sex chromosomes in speciation and hybridization. A previously described population of Finnish Formica wood ants displays genome‐wide signs of ploidally and sexually antagonistic selection resulting from hybridization. Here, hybrid females have increased survivorship but hybrid males are inviable. To understand how the unusual hybrid population may be maintained, we developed a mathematical model with hybrid incompatibility, female heterozygote advantage, recombination and assortative mating. The rugged fitness landscape resulting from the co‐occurrence of heterozygote advantage and hybrid incompatibility results in a sexual conflict in haplodiploids, which is caused by the ploidy difference. Thus, whereas heterozygote advantage always promotes long‐term polymorphism in diploids, we find various outcomes in haplodiploids in which the population stabilizes either in favour of males, females or via maximizing the number of introgressed individuals. We discuss these outcomes with respect to the potential long‐term fate of the Finnish wood ant population and provide approximations for the extension of the model to multiple incompatibilities. Moreover, we highlight the general implications of our results for speciation and hybridization in haplodiploids versus diploids and how the described fitness relationships could contribute to the outstanding role of sex chromosomes as hotspots of sexual antagonism and genes involved in speciation.